Ens primum cognitum in Thomas Aquinas and the tradition : the philosophy of being as first known - Kemple, Brian A. (Value Inquiry Book Series, 2017)
Ens Primum Cognitum in Thomas Aquinas and the Tradition presents a reading of Thomas Aquinas' claim that "being" is the first object of the human intellect. Blending the insights of both the early Thomistic tradition (c.1380-1637AD) and the Leonine Thomistic revival (1879-present), Brian Kemple examines how this claim of Aquinas has been traditionally understood, and what is lacking in that understanding. While the recent tradition has emphasized the primacy of the real (so-called ens reale ) in human recognition of the primum cognitum , Kemple argues that this misinterprets Aquinas, thereby closing off Thomistic philosophy to the broader perspective needed to face the philosophical challenges of today, and proposes an alternative interpretation with dramatic epistemological and metaphysical consequences.